Aspek Lingkungan pada Kualitas Hidup Masyarakat yang Tinggal di Sekitar Tempat Penampungan Sampah: Literature Review - Salma Alya Ihsan; Winda Trijayanthi Utama; Suharmanto Suharmanto; Fitria Saftarina (Fakultas Kedokteran Universitas Lampung, 2024)
Quality of life is an important indicator in assessing a person's ability to live life, which includes four domains; physical health, psychological health, social relationships, and the environment. For people living around landfills, quality of life often decreases due to direct exposure to piles of waste and the pollution it causes. Research shows that the presence of landfills near residential areas is associated with low quality of life, especially in physical and environmental aspects. Pollutants from waste, both organic, inorganic, and biological, can pollute water and soil, and cause health risks, such as malaria, cholera, diarrhea, and respiratory disorders such as asthma and bronchitis. Burning waste in the open, which is common in developing countries, also increases air pollution, releasing hazardous substances, including dioxins and greenhouse gases, which have the potential to cause respiratory health problems and cancer. The impact of this pollution is not only limited to physical health, but also affects mental well-being. People living near landfills often experience emotional instability, feelings of irritability, and tension due to an uncomfortable environment. In addition, irregular environmental conditions, including scattered waste, trigger deviant social actions. Factors such as poor access to sanitation and water contamination also play a role in increasing vulnerability to waterborne and soil-borne diseases. Overall, pollution from landfills has a significant impact on people's quality of life, affecting their physical, psychological and social health.